The Quandary of the Quadricuspid Aortic Valve—The “Unlucky” 4-Leaf Clover: Case Report and Brief Clinical Review - Rajeev Virender Seecheran MBBS (Journal of Investigative Medicine High Impact Case Reports, 2020)
The quadricuspid aortic valve is an exceedingly rare congenital valvular anomaly, characterized by a tetrad of leaflets that typically presents with aortic regurgitation. Almost one third of cases are associated with coexisting cardiac defects with one fifth warranting surgical intervention. In this article, we describe the first documented-in-Caribbean case and present a brief clinical review of its pathophysiology, diagnosis, and management.